Banco de semillas de retamo espinoso Ulex europaeus L. en bordes del matorral invasor en un ecosistema zonal de bosque altoandino, Colombia (2017)
The seed density of Ulex europaeus was established on borders of invasive scrub thickets to the south of the Eastern Hills of Bogota. Through the direct counting method, seed abundance was established at six sampling points in an altitudinal gradient between 2,300 and 3,200 meters altitude, and for four soil depth ranges of 0 to 20 cm. Variable seed densities were established for the six sampling points between 109 and 3.384 seeds m-2. With regard to depth, the highest seed density was in the range of 0 to 5 cm for all sites sampled. Among the sampling points, significant differences were found in the number of seeds at different altitudes (p = 0.4159) and depth ranges evaluated (p=0.3919). There is a high potential at the edges of scrub for the extension of the invaded areas, by activation of the seed bank of the invasive species, suggesting the need for a priority strategy for the control of these border areas in the framework of ecological restoration processes in high Andean ecosystems.